Genetic testing of athletes - Williams, A. G.; Wackerhage, H. (Genetics and Sports, 2009)
This chapter addresses the potential use of genetic tests to predict performance and/or risk of exercise-related injury or illness. Various people may wish to conduct a sport-related genetic test on themselves, or on another person, for a variety of reasons. For example, an individual may seek personal genetic information to assist with choosing their own sporting participation or career. A sports coach may wish to test young team members to assist in selection for a professional career or to individualise training. A physician may want to predict risk of injury or illness in an athlete and advise regarding selection or preventative measures. An insurance company may seek to estimate risk of career-threatening injury or illness to an athlete based partly on genetic information. Despite the commercial availability of some genetic tests today, the evidence currently available suggests that few of these or similar scenarios are scientifically justified - the genetic tests available at the moment are simply not powerful enough to inform important decisions in sport. Furthermore, there are many challenging ethical issues to be addressed regarding genetic testing of athletes. The imposition of genetic tests on individuals by third parties, and particularly the imposition of genetic tests on young people, is potentially susceptible to abuse. There should be considerable further debate regarding these issues so that the tests already available, and the more powerful ones that are likely to emerge as knowledge and genetic technology improve, are only used in acceptable ways. (Autorreferat)